The role of teacher-student relationships in predicting teachers' personal accomplishment and emotional exhaustion. (December 2019) - Corbin, Catherine M.; Alamos, Pilar; Lowenstein, Amy E.; Downer, Jason T.; Brown, Joshua L.
Abstract: Teaching is a uniquely stressful profession. Though previous work has drawn attention to the high levels of burnout teachers report experiencing and its impact on students, comparatively less work has investigated what influences teachers' burnout itself. Guided by Lazarus' (1991) transactional model of stress and coping, the present study explored the links between the proximal resource of teachers' relationships with students and burnout. Specifically, we investigated the association between classroom aggregated teacher reports of relational closeness and conflict, and two components of burnout: personal accomplishment and emotional exhaustion. Results indicated that teachers who reported close relationships with their students also reported higher levels of personal accomplishment over the academic year, whereas more conflictual relationships were associated with increased emotional exhaustion. Implications for relational quality with students as a central influence on teachers' wellbeing are discussed. Highlights: Closeness with students predicted increased teacher personal accomplishment. Conflict with students predicted increased teacher emotional exhaustion. Extreme conflict was not associated with teachers' personal accomplishment.